2017
DOI: 10.3390/su9091564
|View full text |Cite
|
Sign up to set email alerts
|

What Makes Firms Innovative? The Role of Social Capital in Corporate Innovation

Abstract: This paper offers a social capital explanation for the purported relationship between human capital investment and an organization's innovation capability. We argue that social capital plays a mediating role in the relationship between the level of individual knowledge of employees and organizations' innovation capabilities. The mediating mechanism is attributed to the role of social capital in knowledge exchange and combination that help enhance knowledge creation. Using survey data of 319 manufacturing firms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 139 publications
1
38
0
Order By: Relevance
“…According to [22], the knowledge creation process favors the development of technological innovation capabilities for processes and products, because processes and products can lead to a sustainable competitive advantage. The results of [24] demonstrated that relational and cognitive dimensions of social capital are important mediators in realizing organizational innovation performance. These studies showed the importance of innovative solutions for creating convenient process, focusing on perceived value, attracting more customers, and finally, ensuring customer retention.…”
Section: Conveniencementioning
confidence: 92%
See 1 more Smart Citation
“…According to [22], the knowledge creation process favors the development of technological innovation capabilities for processes and products, because processes and products can lead to a sustainable competitive advantage. The results of [24] demonstrated that relational and cognitive dimensions of social capital are important mediators in realizing organizational innovation performance. These studies showed the importance of innovative solutions for creating convenient process, focusing on perceived value, attracting more customers, and finally, ensuring customer retention.…”
Section: Conveniencementioning
confidence: 92%
“…So, recent studies [22][23][24] tried to explore the relationship between innovation and business competitiveness, especially for e-commerce domain. According to [22], the knowledge creation process favors the development of technological innovation capabilities for processes and products, because processes and products can lead to a sustainable competitive advantage.…”
Section: Conveniencementioning
confidence: 99%
“…When it comes to the underlying processes, research shows that organizational learning and the underlying memory of a company resemble an individuals' learning process [15], and that a company learns and forgets through its members [16]. Studies could show the direct relation between employees' knowledge and the overall corporate knowledge [18,19]. Since both are related, they can influence each other in both directions: individual knowledge of employees can have a direct impact on corporate performance, e.g.…”
Section: Learningmentioning
confidence: 99%
“…Since both are related, they can influence each other in both directions: individual knowledge of employees can have a direct impact on corporate performance, e.g. in case of innovation [19], but also the company could influence an employee's memory by changing the work environment (e.g. using different memory cues [20]).…”
Section: Learningmentioning
confidence: 99%
“…Through analyzing the influence factors of knowledge transfer in R&D alliances, Cummings and Teng [37] find that knowledge characteristics, knowledge absorption capacity, and governance structure are significant, and then put forward corresponding suggestions for knowledge cooperation in R&D alliances. Ahn and Kim [38] conduct structural equation modeling (SEM) analysis to analyze the data of 319 manufacturing firms in South Korea, and the results show that social capital plays a mediating role in the relationship between the level of individual knowledge of employees and organizations' capabilities. Based on multiple case studies of knowledge leakage in joint R&D projects in large firms in Sweden, Frishammar et al [19] propose that the dark side of knowledge transfer is knowledge leakage, which will deter knowledge sharing.…”
Section: Knowledge Sharing Behavior Among Enterprisesmentioning
confidence: 99%